Navigating Leadership in the Gen Z Era: Strategies for Inspiring and Engaging a Digital Generation - Syafrayani, Putri Rizki; Lubis, Fauziah Khairani; Siregar, Masitowarni (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2025)
The increasing presence of Generation Z (Gen Z) in the workforce has necessitated a shift in leadership strategies to effectively engage and inspire this digital-native generation. Gen Z employees prioritize autonomy, technological integration, and purpose-driven work, which challenges traditional leadership models. This study explores the most effective leadership approaches for managing Gen Z, focusing on transformational, laissez-faire, and participative leadership styles. The research employs a literature review methodology, synthesizing existing studies on leadership theories, workplace behaviors, and generational expectations. Findings indicate that Gen Z employees thrive in flexible, digitally connected, and ethically conscious work environments. Transformational leadership, which emphasizes mentorship and motivation, proves particularly effective, while laissez-faire leadership supports their need for independence. However, a balanced approach is necessary, as Gen Z also requires structured feedback and career development opportunities. The study concludes that organizations must adopt adaptive, technology-driven, and value-oriented leadership models to attract and retain Gen Z employees. Leaders who embrace digital tools, corporate social responsibility, and continuous learning will create a dynamic and motivated workforce that fosters innovation and long-term success.